Low-carbon 3D printing alkali-activated composite cement mortar and preparation method thereof
By using sodium carbonate and citrate as excitants, combined with specific components and stirring processes, the problems of high carbon emissions and poor safety of alkali-excited composite cement in the prior art are solved, and the preparation of low-carbon and safe 3D printed alkali-excited composite cement mortar is achieved.
Patent Information
- Application Number
- CN202411786542.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, when using high concentrations of sodium hydroxide solution and sodium silicate solution as excitation agents to prepare alkali-excited composite cement, carbon emissions are high and safety is poor.
Sodium carbonate and citrate are used as excitants, combined with low-calcium fly ash, granulated blast furnace slag, ordinary silicate cement and quartz sand, and low-carbon 3D printed alkali-excited composite cement mortar is prepared through a specific stirring process.
The construction strength and uniform density of the prepared alkali-excited composite cement mortar are improved, carbon emissions are reduced, and safety is improved.
Smart Images

Figure CN119591366A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of 3D printing concrete, and in particular to a low-carbon 3D printing alkali-activated composite cement mortar and a preparation method thereof. Background Art
[0002] In recent years, 3D printing technology has been widely used in architectural design, industrial manufacturing, aerospace, bioengineering, cultural relics protection and other industries due to its advantages of low cost, high efficiency, strong design and reliable quality. In particular, the combination of 3D printing technology and concrete technology has provided new ideas for the development and application of concrete materials. This is a new construction technology that uses mechatronics technology to automatically build cement-based building materials layer by layer into the designed model structure. This technology promotes the intelligent and sustainable development of the civil engineering industry.
[0003] Traditional 3D printing concrete materials are usually cement-based or geopolymer-based materials. Cement-based materials have problems of high carbon emissions and poor durability, while geopolymer-based materials have problems such as high shrinkage, excessive shrinkage, and alkali-aggregate reaction. Alkali-activated composite cement combines the advantages of both. It is not only low-carbon and environmentally friendly but also has a denser microstructure.
[0004] Alkali-activated composite cement usually contains a large amount of industrial solid waste (80%) and a small amount of cement (20%), and is activated by an alkali activator. Alkali-activated composite cement can make use of a large amount of industrial solid waste, which plays an important role in saving resources and protecting the environment. In traditional alkali-activated composite cement systems, high-concentration sodium hydroxide solutions and sodium silicate solutions are often used as activators, which is not only not conducive to environmental protection, but also easily causes safety problems. Therefore, the development of low-carbon and safe alkali-activated cement has become a problem that needs to be solved. Summary of the invention
[0005] To this end, the present invention provides a low-carbon 3D printed alkali-activated composite cement mortar and a preparation method thereof, so as to overcome the problems of high carbon emissions and poor safety in the prior art of using high-concentration sodium hydroxide solution and sodium silicate solution as activators to prepare alkali-activated composite cement.
[0006] To achieve the above objectives, on the one hand, the present invention provides a low-carbon 3D printing alkali-activated composite cement mortar, which is composed of the following components in parts by weight: 400 to 500 parts of low-calcium fly ash, 300 to 400 parts of granulated blast furnace slag, 180 to 220 parts of ordinary Portland cement, 1400 to 1600 parts of quartz sand, 47.5 parts of solid sodium carbonate, 10 parts of solid citrate and 359 to 370 parts of water.
[0007] Furthermore, the low-calcium fly ash comprises 35% to 50% SiO2, 15% to 25% Al2O3 and 9% to 10% CaO;
[0008] The granulated blast furnace slag comprises 40% to 50% of CaO, 20% to 30% of SiO2 and 10% to 20% of Al2O3;
[0009] The components of the ordinary Portland cement are: 60% to 70% Cao, 10% to 20% SiO2 and 5% to 10% Al2O3.
[0010] Furthermore, the water consumption of the alkali activator in the mortar is calculated according to the water-binder ratio of 0.34, and the alkali activator is obtained by mixing 4.75% of sodium carbonate and 1% of citrate with water.
[0011] On the other hand, the present invention also provides a method for preparing a composite cement mortar, comprising:
[0012] Step S1, preparing an alkaline activator using solid sodium carbonate, citrate and water as raw materials, and allowing to stand at room temperature;
[0013] Step S2, preparing low-calcium fly ash, granulated blast furnace slag, Portland cement and quartz sand according to a preset ratio and stirring and mixing them evenly;
[0014] Step S3, adding the alkali activator after standing and continuing to stir, stirring and mixing initially after slow stirring, and then stirring and mixing rapidly to obtain low-carbon 3D printing alkali-activated composite cement mortar.
[0015] Furthermore, in the step S1, the base activator is obtained by the following method:
[0016] 4.75% of solid sodium carbonate and 1% of solid citrate are mixed with a predetermined content of water to obtain the base activator.
[0017] Furthermore, in the step S2, it includes:
[0018] Step S21, crushing and grinding the granulated blast furnace slag and quartz sand respectively, and obtaining the average particle sizes of the granulated blast furnace slag and quartz sand respectively;
[0019] Step 22, determining a first stirring time and a first stirring speed according to average particle sizes of the granulated blast furnace slag and the quartz sand;
[0020] Step S23, preparing low-calcium fly ash, silicate cement, crushed and ground granulated blast furnace slag and quartz sand according to a preset ratio, and stirring them once based on the first stirring time and the first stirring speed to obtain a first mixture after stirring and mixing.
[0021] Furthermore, in the step S3, it includes:
[0022] Step S31, determining a second stirring speed according to the bulk density of the first mixture, adding the alkaline activator after standing to the first mixture, and performing secondary stirring and preliminary dispersion mixing based on the second stirring speed to obtain a second mixture;
[0023] Step S32, determining a third stirring speed according to the porosity of the second mixture, and performing stirring and mixing three times based on the third stirring speed to obtain a low-carbon 3D printed alkali-activated composite cement mortar.
[0024] Furthermore, in the step S22, it includes:
[0025] Step S221, determining a first difference value according to a difference value between an average particle size of the granulated blast furnace slag and an average particle size of the quartz sand;
[0026] Step S222, comparing the first difference with a preset difference, and determining a first stirring time and a first stirring speed according to the comparison result.
[0027] Further, in the step S31, determining the second stirring speed includes:
[0028] The bulk density is compared with a preset bulk density, and a second stirring speed is determined according to the comparison result and a standard stirring speed.
[0029] Further, in the step S32, determining the third stirring speed includes:
[0030] The porosity is compared with a preset porosity, and a third stirring speed is determined according to the comparison result and the second stirring speed.
[0031] Compared with the prior art, the invention has the beneficial effect that the invention uses sodium carbonate and citrate for activation, which can improve safety and reduce carbon emissions. The components use low-calcium fly ash, granulated blast furnace slag, ordinary Portland cement and quartz sand, which can improve the construction strength and uniform density of the prepared alkali-activated composite cement mortar.
[0032] Furthermore, the present invention determines the first stirring time and the first stirring speed according to the average particle size of the granulated blast furnace slag and the quartz sand for one stirring, which can improve the stirring uniformity and production efficiency of each component before alkali excitation. By adding an alkali activator to the first mixture, the activity of each component can be highly stimulated, reducing carbon emissions. By determining the second stirring speed according to the bulk density of the first mixture for a second stirring, the alkali activator can be initially contacted with the components of the first mixture, and the alkali activator can be gradually infiltrated into the first mixture. By determining the third stirring speed according to the porosity of the second mixture for three stirrings, the components of the second mixture can be fully contacted and reacted, thereby improving the density and construction performance of the prepared alkali-activated composite cement mortar.
[0033] Furthermore, the alkali activator of the present invention uses 1% solid citrate, which can improve the slow setting property of the alkali activator, thereby improving the strength of the prepared alkali-activated composite cement mortar, and uses 4.75% solid sodium carbonate, which can reduce carbon emissions and improve safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a flow chart of a method for preparing composite cement mortar according to an embodiment of the present invention;
[0035] Figure 2 Schematic diagram of the process of step S2 of the embodiment of the present invention;
[0036] Figure 3 Schematic diagram of the process of step S3 of the embodiment of the present invention;
[0037] Figure 4 Schematic diagram of initial setting time, fluidity and compressive strength of alkali-activated composite cement mortar with different contents of sodium citrate added in an embodiment of the present invention;
[0038] Figure 5 A comparison chart of carbon emission indexes of alkali-activated composite cement mortar, traditional geopolymer mortar, and ordinary Portland cement mortar with different proportions in the embodiments of the present invention;
[0039] Figure 6 It is a comparison chart of the cost indexes of alkali-activated composite cement mortar, traditional geopolymer mortar and ordinary Portland cement mortar with different proportions according to the embodiments of the present invention. DETAILED DESCRIPTION
[0040] In order to make the objects and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with embodiments; it should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0041] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.
[0042] It should be noted that, in the description of the present invention, terms such as "up", "down", "left", "right", "inside" and "outside" indicating directions or positional relationships are based on the directions or positional relationships shown in the drawings. This is merely for the convenience of description and does not indicate or imply that the device or element must have a specific orientation, be constructed and operated in a specific orientation. Therefore, it cannot be understood as a limitation on the present invention.
[0043] In addition, it should be noted that in the description of the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For those skilled in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0044] The embodiment of the present invention provides a low-carbon 3D printed alkali-activated composite cement mortar, comprising: a cementitious material, an aggregate, and an alkali activator; the cementitious material comprises low-calcium fly ash, granulated blast furnace slag, and ordinary Portland cement, the aggregate comprises quartz sand, and the alkali activator comprises sodium carbonate, citrate, and water;
[0045] The mortar is composed of the following components in parts by weight: 400 to 500 parts of low-calcium fly ash, 300 to 400 parts of granulated blast furnace slag, 180 to 220 parts of ordinary Portland cement, 1400 to 1600 parts of quartz sand, 47.5 parts of solid sodium carbonate, 10 parts of solid citrate and 359 to 370 parts of water.
[0046] Specifically, the low-calcium fly ash comprises 35% to 50% SiO2, 15% to 25% Al2O3 and 9% to 10% CaO;
[0047] The granulated blast furnace slag comprises 40% to 50% of CaO, 20% to 30% of SiO2 and 10% to 20% of Al2O3;
[0048] The components of the ordinary Portland cement are: 60% to 70% Cao, 10% to 20% SiO2 and 5% to 10% Al2O3.
[0049] Specifically, the amount of water used for the alkali activator in the mortar is calculated based on a water-binder ratio of 0.34, and the alkali activator is obtained by mixing 4.75% of sodium carbonate and 1% of citrate with water.
[0050] It is understood that the water-to-binder ratio is the ratio of the mass of water to the total mass of the colloid mixture, wherein the colloid mixture includes a gelling material, solid sodium carbonate and solid citrate. 4.75% is the ratio of the mass of sodium carbonate in the alkali activator to the mass of the gelling material, and 1% is the ratio of the mass of citrate in the alkali activator to the mass of the gelling material.
[0051] The present invention uses sodium carbonate and citrate for activation, which can improve safety and reduce carbon emissions. The components use low-calcium fly ash, granulated blast furnace slag, ordinary Portland cement and quartz sand, which can improve the construction strength and uniform density of the prepared alkali-activated composite cement mortar.
[0052] See also Figure 1 As shown, it is a flow chart of a method for preparing a composite cement mortar according to an embodiment of the present invention; an embodiment of the present invention also provides a method for preparing a composite cement mortar, comprising:
[0053] Step S1, preparing an alkaline activator using solid sodium carbonate, citrate and water as raw materials, and allowing to stand at room temperature;
[0054] See also Figure 4 As shown, it is a schematic diagram of the initial setting time, fluidity and compressive strength of the alkali-activated composite cement mortar with different contents of citrate added in the embodiment of the present invention;
[0055] Specifically, in step S1, the base activator is obtained by the following method:
[0056] 4.75% of solid sodium carbonate and 1% of solid citrate are mixed with a predetermined content of water to obtain the base activator.
[0057] In implementation, the water-binder ratio is the ratio of the mass of water to the total mass of the colloid mixture, wherein the colloid mixture includes a cementitious material, solid sodium carbonate and solid citrate, and the preset content can be calculated based on the water-binder ratio. Preferably, the water-binder ratio is set in the range of 0.3 to 0.5.
[0058] It is understandable that 1% of citrate has a significant retarding effect and strength-enhancing effect, which can increase the initial setting time by 100% and the strength by about 25%, which results in better extrudability and construction properties of alkali-activated composite cement mortar. For example, the citrate can be selected from sodium citrate, potassium citrate, etc. Preferably, sodium citrate is selected. The mechanism of action of sodium citrate as a retarder in alkali-activated composite cement is mainly through the interaction with the reaction products of aluminosilicate minerals in the system, thereby delaying the hardening process of geopolymers. Specifically, sodium citrate is an organic molecule that can react with aluminum ions (Al 3+ ), silicon ions (SiO4 4- ) and alkali metal ions (such as Na + ) interactions. These interactions may include: (1) Complexation. Sodium citrate can form stable complexes with aluminum ions, which will reduce the concentration of free aluminum ions and affect the dissolution and recrystallization process of aluminosilicate minerals. Since aluminum is one of the key components of the geopolymer network structure, changes in its concentration will affect the formation rate of the polymer network, resulting in a prolonged setting time. (2) Adsorption. Sodium citrate may be adsorbed on the surface of the alkali-activated composite cement particles being formed, hindering the further deposition and connection of other ions, thereby slowing down the growth rate of the alkali-activated composite cement network. (3) pH adjustment. The addition of sodium citrate may also change the pH value of the system, and the pH value has an important influence on the solubility of aluminosilicate minerals and the formation of alkali-activated composite cement. Changes in pH can indirectly affect the setting rate. (4) Crystal formation and growth inhibition. The presence of sodium citrate will affect the nucleation and crystal growth process of cement hydration products, especially for early-formed hydration products such as ettringite (AFt) and monosulfide hydrated calcium sulfoaluminate (AFm). By inhibiting the formation of these early hydration products, the setting time of the slurry can be delayed.
[0059] The alkali activator of the present invention adopts 1% solid citrate, which can improve the slow setting property of the alkali activator, thereby improving the strength of the prepared alkali-activated composite cement mortar. The alkali activator adopts 4.75% solid sodium carbonate, which can reduce carbon emissions and improve safety.
[0060] Step S2, preparing low-calcium fly ash, granulated blast furnace slag, Portland cement and quartz sand according to a preset ratio and stirring and mixing them evenly;
[0061] See also Figure 2 As shown, it is a flow chart of step S2 of an embodiment of the present invention; specifically, in step S2, it includes:
[0062] Step S21, crushing and grinding the granulated blast furnace slag and quartz sand respectively, and obtaining the average particle sizes of the granulated blast furnace slag and quartz sand respectively;
[0063] It should be noted that those skilled in the art are aware that any device and method in the prior art that can obtain the average particle size of granulated blast furnace slag and quartz sand falls within the protection scope of the present invention and will not be described in detail herein.
[0064] Step 22, determining a first stirring time and a first stirring speed according to average particle sizes of the granulated blast furnace slag and the quartz sand;
[0065] Specifically, in step S22, it includes:
[0066] Step S221, determining a first difference value according to a difference value between an average particle size of the granulated blast furnace slag and an average particle size of the quartz sand;
[0067] Step S222, comparing the first difference with a preset difference, and determining a first stirring time and a first stirring speed according to the comparison result.
[0068] Wherein, if the first difference is less than a preset difference, the standard stirring time is determined as the first stirring time, and the standard stirring speed is determined as the first stirring speed;
[0069] If the first difference is greater than or equal to a preset difference, the first stirring time and the first stirring speed are determined according to a ratio of the first difference to the preset difference, a standard stirring time, and a standard stirring speed.
[0070] It can be understood that the difference between the average particle size of the granulated blast furnace slag and the average particle size of the quartz sand can characterize the difference in particle size distribution of the two materials. When the difference between the average particle size of the granulated blast furnace slag and the average particle size of the quartz sand is large, it means that the difference in particle size distribution of the two materials is large, which will increase the friction and resistance during stirring. Therefore, a greater stirring speed and a longer stirring time are required to ensure that the components are fully mixed. The actual implementers can determine the preset difference based on the actual situation or based on the average of the difference between the average particle size of the granulated blast furnace slag corresponding to the alkali-activated composite cement mortar that has passed the qualification test and the average particle size of the quartz sand in the historical data. Preferably, the preset difference value range is set to 10μm to 50μm.
[0071] In practice, the average particle size of the quartz sand is 250 μm to 900 μm, and the average particle size of the granulated blast furnace slag is 10 μm to 100 μm.
[0072] In a specific embodiment, when the first difference is greater than or equal to the preset difference, the first ratio can be determined according to the ratio of the first difference to the preset difference, the first stirring time can be determined according to the product of the first ratio and the standard stirring time, and the first stirring speed can be determined according to the product of the first ratio and the standard stirring speed. The first stirring time and the first stirring time speed can also be determined according to the difference between the first difference and the preset difference, as long as the first stirring time is positively correlated with the difference between the first difference and the preset difference, and the first stirring speed is positively correlated with the difference between the first difference and the preset difference. The specific adjustment amount can be determined according to the actual scenario through several tests, which will not be repeated here.
[0073] It can be understood that the actual implementers can set the standard mixing time and standard mixing speed according to the actual situation or based on the mixing time and mixing speed of the alkali-activated composite cement mortar that has passed the qualification test in historical data. Preferably, the standard mixing time value range is set to 10min~20min, and the standard mixing speed value range is set to 30r / min~40r / min.
[0074] Step S23, preparing low-calcium fly ash, silicate cement, crushed and ground granulated blast furnace slag and quartz sand according to a preset ratio, and stirring them once based on the first stirring time and the first stirring speed to obtain a first mixture after stirring and mixing.
[0075] Step S3, adding the alkali activator after standing and continuing to stir, stirring and mixing initially after slow stirring, and then stirring and mixing rapidly to obtain low-carbon 3D printing alkali-activated composite cement mortar.
[0076] See also Figure 3 As shown, it is a flow chart of step S3 of an embodiment of the present invention; specifically, in step S3, it includes:
[0077] Step S31, determining a second stirring speed according to the bulk density of the first mixture, adding the alkaline activator after standing to the first mixture, and performing secondary stirring and preliminary dispersion mixing based on the second stirring speed to obtain a second mixture;
[0078] Specifically, in the step S31, determining the second stirring speed includes:
[0079] The bulk density is compared with a preset bulk density, and a second stirring speed is determined according to the comparison result and a standard stirring speed.
[0080] It can be understood that the bulk density of the first mixture can characterize its compactness in the bulk state. The larger the bulk density, the greater the compactness in the bulk state, and the greater the friction between the particles. In order to fully mix it with the added alkali activator, a greater stirring speed is required during stirring to ensure that the components are fully mixed.
[0081] In implementation, if the bulk density (mass of material per unit volume) is less than the preset bulk density, the standard stirring speed is determined as the second stirring speed; if the bulk density is greater than or equal to the preset bulk density, the second ratio is determined based on the ratio of the bulk density to the preset bulk density, and the second stirring speed is determined based on the product of the second ratio and the standard stirring speed.
[0082] It is understandable that the actual implementer can set the preset bulk density according to the actual situation or based on the average bulk density of the first mixture corresponding to the alkali-activated composite cement mortar that has passed the qualification test in historical data, and the value range of the preset bulk density is set to 1200kg / m 3 ~1400kg / m 3 .
[0083] It should be noted that those skilled in the art are aware that any device and method in the prior art that can calculate the bulk density of the first mixture falls within the protection scope of the present invention and will not be described in detail herein.
[0084] Step S32, determining a third stirring speed according to the porosity of the second mixture, and performing stirring and mixing three times based on the third stirring speed to obtain a low-carbon 3D printed alkali-activated composite cement mortar.
[0085] Specifically, in step S32, determining the third stirring speed includes:
[0086] The porosity is compared with a preset porosity, and a third stirring speed is determined according to the comparison result and the second stirring speed.
[0087] It can be understood that the greater the porosity of the second mixture, the larger the pores between the particles of the second mixture components, the smaller the degree of compactness, and the more / larger the pores contained inside. In order to eliminate the pores, a greater stirring speed is required to increase the amount and speed of gas exclusion inside the second mixture.
[0088] In implementation, the second difference is determined according to the difference between the porosity and the preset porosity, the third ratio is determined according to the ratio of the second difference to the preset porosity, and the adjustment amplitude is determined according to the product of the third ratio and the second stirring speed, that is, the third stirring speed is the sum of the second stirring speed and the adjustment amplitude.
[0089] It should be noted that those skilled in the art are aware that any device and method in the prior art capable of detecting the porosity of the second mixture falls within the protection scope of the present invention and will not be described in detail herein.
[0090] It is understandable that the actual implementer can set the preset porosity according to the actual situation or based on the average porosity of the second mixture corresponding to the alkali-activated composite cement mortar that has passed the qualification test in the historical data, or can use the porosity prediction value corresponding to the packing density predicted by data training as the preset porosity, or calculate the preset porosity KX according to the following formula:
[0091] KX=1-DM / ZM,
[0092] Wherein, DM is the preset bulk density, and ZM is the particle density of the first mixture.
[0093] Preferably, the preset porosity value range is set to 10% to 15%.
[0094] It is understandable that the above-mentioned stirring operation can be achieved by any mixing and stirring equipment that can stir the alkali-activated composite cement mortar, such as a planetary mixer. This is a prior art and will not be described in detail.
[0095] In a specific embodiment, the hydration product of the present invention includes a mixture of CSH (calcium silicate hydrate) gel, the main reaction product of cement hydration, and NASH (sodium aluminosilicate hydrate), the main hydration product of alkali-activated cementitious material, which is a three-dimensional structure gel with a higher degree of polymerization and more cross-linked silicon. In addition, the hydration heat released by cement hydration accelerates the alkali activation reaction at room temperature. Therefore, the early strength and hardening rate of the present invention are improved, and the specific hydration process is as follows:
[0096] (1) Initial stage:
[0097] In the initial stage, when the alkali activated composite cement is mixed with water, the alkaline solution (sodium carbonate solution) begins to penetrate into the raw material particles. This stage is mainly the initial contact between the alkali solution and the active components in the raw materials (such as silicates and aluminosilicates), and begins to dissolve soluble silicate and aluminosilicate ions.
[0098] (2) Dissolution and activation stage:
[0099] As the alkaline solution penetrates further, the active components in the raw materials begin to dissolve, forming soluble silicate and aluminosilicate ions. These ions become more active under alkaline conditions and begin to interact with other ions (such as sodium ions and potassium ions) to form new hydration products. This stage is crucial for the formation of the final gel-like substance.
[0100] (3) Gel formation stage:
[0101] At this stage, the dissolved silicate and aluminosilicate ions begin to rearrange and form a three-dimensional gel network structure, which is composed of silicon-oxygen tetrahedron (SiO4 4- ) and aluminum oxide tetrahedron (AlO4 5- ), these gel networks gradually grow and eventually form the main structure of the geopolymer;
[0102] (4) Hardening stage:
[0103] Over time, the gel network gradually hardens to form a solid material with mechanical strength. In this process, the undissolved particles continue to dissolve and combine with the formed gel network, further enhancing the overall strength of the material. At the same time, excess water is gradually removed and the material becomes denser.
[0104] (5) Mature stage:
[0105] In the final maturity stage, the physical and chemical properties of the material tend to stabilize and the strength continues to grow until it reaches its maximum value. This stage may last for weeks or even months, depending on the specific material composition and curing conditions.
[0106] It is understood that the hydration product of alkali-activated composite cement is a mixture of CSH gel, the main reaction product of cement hydration, and NASH, the main hydration product of alkali-activated cementitious materials. However, CSH and NASH gels can change their composition during the reaction. When there is enough calcium and alumina in the solution and the pH value is greater than 12, CSH and NASH gels will evolve into CASH (hydrated calcium aluminosilicate) and (N, C)-ASH (hydrated aluminosilicate containing both sodium and calcium elements), respectively. They are three-dimensional structured gels with a high degree of polymerization and cross-linked silicon. In addition, the hydration heat released by cement hydration accelerates the alkali activation reaction of alkali-activated composite cement at room temperature, so the early strength and hardening rate of alkali-activated composite cement are improved.
[0107] Embodiment 1:
[0108] The components of this embodiment include, by weight, 500 parts of low-calcium fly ash, 300 parts of granulated blast furnace slag, 200 parts of ordinary Portland cement, 1500 parts of quartz sand, 47.5 parts of solid sodium carbonate, 10 parts of solid sodium citrate and 359 parts of water. The alkali-activated composite cement mortar suitable for 3D printing is prepared by the composite cement mortar preparation method of the present invention. After testing, the alkali-activated composite cement mortar provided by this embodiment has a 28-day compressive strength of more than 35 MPa, wherein the 3D printed specimen has a compressive strength of 43 MPa in the X direction, 42 MPa in the Y direction, and 48 MPa in the Z direction, a fluidity of about 200 mm, and a static yield stress of about 2200 Pa when standing for 10 minutes. In the constructive test of 3D printing, a total of 17 layers were printed, and the height was about 16 cm before collapsing.
[0109] Embodiment 2:
[0110] The components of this embodiment include, by weight, 500 parts of low-calcium fly ash, 300 parts of granulated blast furnace slag, 200 parts of ordinary Portland cement, 1500 parts of quartz sand, 47.5 parts of solid sodium carbonate, 10 parts of solid potassium citrate and 359 parts of water. The alkali-activated composite cement mortar suitable for 3D printing is prepared by the composite cement mortar preparation method of the present invention. After testing, the alkali-activated composite cement mortar provided by this embodiment has a 28-day compressive strength of about 40 MPa, wherein the 3D printed specimen has a compressive strength of 41 MPa in the X direction, 38 MPa in the Y direction, and 44 MPa in the Z direction, a fluidity of about 205 mm, and a static yield stress of about 2300 Pa when standing for 10 minutes. In the constructive test of 3D printing, a total of 15 layers were printed, and the height was about 14.5 cm before collapsing.
[0111] Embodiment 3:
[0112] The components of this embodiment include, by weight, 400 parts of low-calcium fly ash, 400 parts of granulated blast furnace slag, 200 parts of ordinary Portland cement, 1500 parts of quartz sand, 47.5 parts of solid sodium carbonate, 10 parts of solid sodium citrate and 370 parts of water. The alkali-activated composite cement mortar suitable for 3D printing is prepared by the composite cement mortar preparation method of the present invention. After testing, the alkali-activated composite cement mortar provided by this embodiment has a 28-day compressive strength of about 38 MPa, wherein the 3D printed specimen has a compressive strength of 43 MPa in the X direction, 40 MPa in the Y direction, and 44 MPa in the Z direction, a fluidity of about 190 mm, and a static yield stress of about 1300 Pa when standing for 10 minutes. In the constructive test of 3D printing, a total of 13 layers were printed, and the height was about 12.5 cm before collapsing.
[0113] Embodiment 4:
[0114] The components of this embodiment include, by weight, 400 parts of low-calcium fly ash, 400 parts of granulated blast furnace slag, 200 parts of ordinary Portland cement, 1500 parts of quartz sand, 47.5 parts of solid sodium carbonate, 10 parts of solid potassium citrate and 370 parts of water. The alkali-activated composite cement mortar suitable for 3D printing is prepared by the composite cement mortar preparation method of the present invention. After testing, the alkali-activated composite cement mortar provided by this embodiment has a 28-day compressive strength of about 38 MPa, wherein the 3D printed specimen has a compressive strength of 44 MPa in the X direction, 40 MPa in the Y direction, and 46 MPa in the Z direction, a fluidity of about 195 mm, and a static yield stress of about 1150 Pa when standing for 10 minutes. In the constructive test of 3D printing, a total of 10 layers were printed, and the height was about 10 cm before collapsing.
[0115] Comparative Example:
[0116] The components of this embodiment include, by weight, 400 parts of low-calcium fly ash, 400 parts of granulated blast furnace slag, 200 parts of ordinary Portland cement, 1500 parts of quartz sand, 47.5 parts of solid sodium hydroxide, 10 parts of solid sodium silicate and 370 parts of water. The alkali-activated composite cement mortar (wherein the alkali activator is prepared from solid sodium hydroxide, solid sodium silicate and water) is also prepared by the composite cement mortar preparation method of the present invention. After testing, the alkali-activated composite cement mortar provided by this comparative example has a 28-day compressive strength of about 15 MPa, wherein the 3D printed specimen has a compressive strength of 20 MPa in the X direction, 21 MPa in the Y direction, and 25 MPa in the Z direction, and a fluidity of about 195 mm. The static yield stress is about 1150 Pa when standing for 10 minutes. In the constructive test of 3D printing, a total of 7 layers were printed, and the height was about 6.5 cm before collapsing.
[0117] It can be seen from the above embodiments and comparative examples that the alkali-activated composite cement mortar activated by sodium carbonate and citrate can meet the requirements of 3D printed concrete and can have higher strength, thus realizing low-carbon and safe alkali-activated composite cement mortar.
[0118] See also Figure 5 and Figure 6 As shown, Figure 5 A comparison chart of carbon emission indexes of alkali-activated composite cement mortar, traditional geopolymer mortar, and ordinary Portland cement mortar with different proportions in the embodiments of the present invention; Figure 6 It is a comparison chart of the cost indexes of alkali-activated composite cement mortar, traditional geopolymer mortar and ordinary Portland cement mortar with different proportions according to the embodiments of the present invention.
[0119] As can be seen from the figure, the carbon emission index (4.75) of the present invention is lower than that of traditional geopolymer mortar (7.97) and cement mortar (27.33), and the cost index (9.57) of the present invention is also lower than that of traditional geopolymer mortar (16.74) and cement mortar (30). The present invention has a good effect on the environment and reduces the material cost of 3D printing.
[0120] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.
Claims
1. A low-carbon 3D printed alkali-activated composite cement mortar, characterized in that: The mortar is composed of the following components in parts by weight: 400 to 500 parts of low-calcium fly ash, 300 to 400 parts of granulated blast furnace slag, 180 to 220 parts of ordinary Portland cement, 1400 to 1600 parts of quartz sand, 47.5 parts of solid sodium carbonate, 10 parts of solid citrate and 359 to 370 parts of water.
2. The low-carbon 3D printing alkali-activated composite cement mortar according to claim 1, characterized in that: The low-calcium fly ash components are 35% to 50% SiO2, 15% to 25% Al2O3 and 9% to 10% CaO; The granulated blast furnace slag comprises 40% to 50% of CaO, 20% to 30% of SiO2 and 10% to 20% of Al2O3; The components of the ordinary Portland cement are: 60% to 70% Cao, 10% to 20% SiO2 and 5% to 10% Al2O3.
3. The low-carbon 3D printing alkali-activated composite cement mortar according to claim 1, characterized in that: The amount of water used for the alkali activator in the mortar is calculated based on a water-binder ratio of 0.34, and the alkali activator is obtained by mixing 4.75% of sodium carbonate and 1% of citrate with water.
4. A method for preparing a composite cement mortar, which is used to prepare the low-carbon 3D printing alkali-activated composite cement mortar according to any one of claims 1 to 3, characterized in that: include: Step S1, preparing an alkaline activator using solid sodium carbonate, citrate and water as raw materials, and allowing to stand at room temperature; Step S2, preparing low-calcium fly ash, granulated blast furnace slag, Portland cement and quartz sand according to a preset ratio and stirring and mixing them evenly; Step S3, adding the alkali activator after standing and continuing to stir, stirring and mixing initially after slow stirring, and then stirring and mixing rapidly to obtain a low-carbon 3D printing alkali-activated composite cement mortar.
5. The method for preparing composite cement mortar according to claim 4, characterized in that: In the step S1, the base activator is obtained by the following method: 4.75% of solid sodium carbonate and 1% of solid citrate are mixed with a predetermined content of water to obtain the base activator.
6. The method for preparing composite cement mortar according to claim 5, characterized in that: In the step S2, it includes: Step S21, crushing and grinding the granulated blast furnace slag and quartz sand respectively, and obtaining the average particle sizes of the granulated blast furnace slag and quartz sand respectively; Step 22, determining a first stirring time and a first stirring speed according to average particle sizes of the granulated blast furnace slag and the quartz sand; Step S23, preparing low-calcium fly ash, silicate cement, crushed and ground granulated blast furnace slag and quartz sand according to a preset ratio, and stirring them once based on the first stirring time and the first stirring speed to obtain a first mixture after stirring and mixing.
7. The method for preparing composite cement mortar according to claim 6, characterized in that: In the step S3, it includes: Step S31, determining a second stirring speed according to the bulk density of the first mixture, adding the alkaline activator after standing to the first mixture, and performing secondary stirring and preliminary dispersion mixing based on the second stirring speed to obtain a second mixture; Step S32, determining a third stirring speed according to the porosity of the second mixture, and performing stirring and mixing three times based on the third stirring speed to obtain a low-carbon 3D printed alkali-activated composite cement mortar.
8. The method for preparing composite cement mortar according to claim 7, characterized in that: In the step S22, it includes: Step S221, determining a first difference value according to a difference value between an average particle size of the granulated blast furnace slag and an average particle size of the quartz sand; Step S222, comparing the first difference with a preset difference, and determining a first stirring time and a first stirring speed according to the comparison result.
9. The method for preparing composite cement mortar according to claim 8, characterized in that: In the step S31, determining the second stirring speed includes: The bulk density is compared with a preset bulk density, and a second stirring speed is determined according to the comparison result and a standard stirring speed.
10. The method for preparing composite cement mortar according to claim 9, characterized in that: In the step S32, determining the third stirring speed includes: The porosity is compared with a preset porosity, and a third stirring speed is determined according to the comparison result and the second stirring speed.